2021
DOI: 10.1177/15347354211002662
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Digoxin and Digitoxin on Cell Growth in Human Ovarian Cancer Cell Line SKOV-3

Abstract: Background: Cardiac glycosides (CGs) possess a chemical structure similar to steroids, and are inhibitors of the sodium potassium pump. An anti-tumor effect of CGs in breast and prostate cancers has been reported, but the effect of CGs on ovarian cancer is still unclear. Aims: In this study, the effects of CGs on proliferation, cytotoxicity and cell cycle of ovarian cancer cell line (SKOV-3) have been investigated. Procedure: The cell proliferation and cytotoxicity were detected by MTT assay and LDH activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“… 1 Effects of digoxin on cancer have been investigated in a variety of in vitro studies, mostly showing anti-cancer properties by causing cell-cycle arrest. 194–200 These findings were supported by in vivo studies, showing inhibition of tumour growth, 200–202 or reducing distant tumour formation. 203 Despite the appealing pre-clinical data, meta-analyses on clinical studies show rather contradictory results.…”
Section: Effects Of Digoxin On Cancermentioning
confidence: 80%
“… 1 Effects of digoxin on cancer have been investigated in a variety of in vitro studies, mostly showing anti-cancer properties by causing cell-cycle arrest. 194–200 These findings were supported by in vivo studies, showing inhibition of tumour growth, 200–202 or reducing distant tumour formation. 203 Despite the appealing pre-clinical data, meta-analyses on clinical studies show rather contradictory results.…”
Section: Effects Of Digoxin On Cancermentioning
confidence: 80%
“…Cell viability and proliferation assay was performed as described previously [36]. Briefly, cells were plated on 24 well plates with a density of 5 × 10 4 .…”
Section: Cell Viability and Proliferation Assaymentioning
confidence: 99%
“…Numerous studies have indicated that sodium pumps are abnormally expressed in various cancers, including CRC, lung cancer, breast cancer, and liver cancer ( 8 , 15 17 ). The sodium pump is a main target of cardiac glycosides, including bufalin and digoxin ( 18 ). Cardiac glycosides, which are therapeutic agents for heart failure treatment, are natural compounds derived from plants and animals, such as Digitalis lanata and Bufo arenarum ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%